Long-term benefit of renal denervation on blood pressure control in a patient with hemorrhagic stroke - Francesco Versaci; Giuseppe Andò; Marcello Chiocchi; Francesco Romeo (SAGE Open Medical Case Reports, 2019)
A 49-year-old man with malignant hypertension had been admitted with hemorrhagic stroke. Refractory hypertension had been observed during hospitalization and the decision had been made to perform renal denervation. A significant blood pressure reduction was obtained immediately after renal denervation and persists at 2-year follow-up. This case demonstrates the long-term sustained efficacy of renal denervation performed in the acute phase of hemorrhagic stroke. In addition, it supports the notion that renal denervation–induced normalization of blood pressure may contribute to better outcomes in a challenging setting such as intracranial bleeding.